Stanley and the magic lamp - Brown, Jeff, 1926-2003.; Nash, Scott, 1959- (New York : Scholastic, Inc., 2003)
The members of the Lambchop family react differently when a boistrous genie grants their wishes for fame, power, and the ability to fly.
Originally published as A lamp for the Lambchops, 1983.
Keywords: Wishes -- Juvenile fiction; Magic -- Juvenile fiction